The Rights of Children and Adolescents, youth, and participation in public policy - Ferlini Salazar, Héctor (2017)
His article approaches the most relevant of Costa Rican political participation along with the mechanisms to include children and young people in the dynamics of participation and citizenship construction. The theme is studied in the light of a categorical elaboration regarding notions about citizenship and how to apply it to concrete reality through political opportunities and participatory instances provided by the State. The use of the term "participation" in the reports of the ‘Estado de los Derechos de la Niñez y la Adolescencia’ and in government documents is specifically analyzed.